Excited states dynamics at pentacene/perfluoropentacene interfaces: a femtosecond time-resolved second harmonic generation study [research data] - Sivanesan, Vipilan; Broch, Katharina; Tegeder, Petra (Universität, 2024)
Understanding the dynamics of excited states after optical excitation at donor-acceptor (D/A) interfaces is of paramount importance for improving the efficiency and performance of optoelectronic devices. Here, we studied the ultrafast excited state dynamics after optical excitation at interfaces between the electron donor (D) pentacene (PEN) and the electron acceptor (A) perfuoropentacene (PFP) as well as within the single compounds (PEN and PFP) using femtosecond (fs) time-resolved second harmonic generation (SHG). In the single compounds singlet fission is observed on a time scale of around 200 fs. In the bilayer systems a huge SHG intensity rise is observed due to the creation of charge transfer states at the interface and accordingly to formation of a local electric field within tens of picoseconds. The local electric field and therefore the SHG signal intensity from the interface of PEN/PFP bilayer is much more intense compared to the PFP/PEN system because the PFP and PEN intermixing at the PEN/PFP interface is higher. Accordingly a population of defect states on a time scale of 55±12 ps has been proposed for PEN/PFP. Our study provides important insights into D/A charge transfer properties, which is needed for the understanding of the interfacial photophysics of pentacene-based organic compounds.